2010
DOI: 10.1158/0008-5472.can-10-0902
|View full text |Cite
|
Sign up to set email alerts
|

Basal and Treatment-Induced Activation of AKT Mediates Resistance to Cell Death by AZD6244 (ARRY-142886) in Braf-Mutant Human Cutaneous Melanoma Cells

Abstract: The majority of melanomas demonstrate constitutive activation of the RAS-RAF-MEK-MAPK pathway. AZD6244 is a selective MEK1/2 inhibitor which markedly reduces tumor P-MAPK levels, but it produced few clinical responses in melanoma patients. An improved understanding of the determinants of resistance to AZD6244 may lead to improved patient selection and effective combinatorial approaches. The effects of AZD6244 on cell growth and survival were tested in a total of 14 Braf-mutant and 3 wild-type human cutaneous m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
211
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(245 citation statements)
references
References 39 publications
32
211
0
Order By: Relevance
“…10,14,[18][19][20][21][22][23] AZD6244 is a benzimidazole and selective 2nd generation MEK inhibitor with reported activity at nanomolar concentrations against purified MEK1 enzyme in preclinical solid tumor studies. [18][19][20][21][22][23] Further, AZD6244 is a noncompetitive MEK inhibitor with preclinical antitumor activity in solid tumor models including hepatocellular, colon, myeloma, thyroid, pancreatic, melanoma, and breast cancers 19,20,41 and tested clinically in phase 1 24 and phase 2 trials of advanced, refractory colorectal, melanoma, and lung cancer. [25][26][27] AZD6244 has been examined in leukemia and myeloma models, [42][43][44] however to our knowledge, has never been tested in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,14,[18][19][20][21][22][23] AZD6244 is a benzimidazole and selective 2nd generation MEK inhibitor with reported activity at nanomolar concentrations against purified MEK1 enzyme in preclinical solid tumor studies. [18][19][20][21][22][23] Further, AZD6244 is a noncompetitive MEK inhibitor with preclinical antitumor activity in solid tumor models including hepatocellular, colon, myeloma, thyroid, pancreatic, melanoma, and breast cancers 19,20,41 and tested clinically in phase 1 24 and phase 2 trials of advanced, refractory colorectal, melanoma, and lung cancer. [25][26][27] AZD6244 has been examined in leukemia and myeloma models, [42][43][44] however to our knowledge, has never been tested in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 ARRY-142886 (AZD6244, selumetinib; Astra Zeneca) is a selective nonATP-competitive 2nd generation oral MEK inhibitor studied primarily in solid tumor studies with reported nanomolar activity against purified MEK1 enzyme. [18][19][20][21][22][23] Furthermore, phase 1 and phase 2 solid tumor clinical trials have shown this agent to be well-tolerated and have encouraging clinical efficacy. [24][25][26][27] To our knowledge, minimal data are available on newer generation MEK inhibitors in lymphoma and moreover, this anti-MEK agent has never been examined in lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Akt has also been shown to mediate resistance to cell death induced by the potent, highly selective, uncompetitive inhibitor of MEK1/2 AZD6244 in melanoma cells harboring a mutant V600E B-Raf. 195 Melanoma cells expressing mutant V600E B-Raf and functional PTEN were found to be sensitive to AZD6244 treatment and showed no elevation in pAkt. 195 However, AZD6244 resistant cells, despite expressing normal PTEN showed elevated pAkt treatment indicating that Akt mediates the resistance to AZD6244.…”
Section: Mechanisms Leading To the Induction Of Drug Resistancementioning
confidence: 98%
“…195 Melanoma cells expressing mutant V600E B-Raf and functional PTEN were found to be sensitive to AZD6244 treatment and showed no elevation in pAkt. 195 However, AZD6244 resistant cells, despite expressing normal PTEN showed elevated pAkt treatment indicating that Akt mediates the resistance to AZD6244. 195 …”
Section: Mechanisms Leading To the Induction Of Drug Resistancementioning
confidence: 98%
See 1 more Smart Citation